Stress corrosion cracking and brittle failure in a fiber-reinforced plastic (FRP) insulator from a 400 kV transmission line in humid environment. (January 2019) - Luder, D.; Ariely, S.; Yalin, M.
Abstract: A fiber-reinforced plastic (FRP) suspension insulator belonging to the Israel Electric Corporation (IECo) failed catastrophically on a 400 kV transmission line during service at the humid south Israeli coastline. The failure occurred during the summer of 2016 after 15 years of service. The suspension had a declared life expectancy of 30 years. The failure resulted in a local outage at a high cost. An investigation was commissioned. The insulator includes a FRP rod with a housing and weather-sheds made of silicon rubber (SiR); the FRP rod is fitted into a metal connector at its end. The fracture occurred 30–40 mm above the metal fitting/grading ring area near the first weather-shed. Macroscopically, the fracture surface was partially characterized by the features of brittle fracture mode in FRP, while the rest of the fracture surface featured severe fiber pullout and debonding. It was also possible to observe that a large crack in the SiR housing led directly to the fracture surface area that included stained and crushed fibers. EDS analysis revealed that the housing around the crack and the stained fibers themselves were polluted with a significant amount of nitrogen, in addition to other foreign pollutants. After surveying similar cases, it was strongly suggested that the source of nitrogen was nitric acid formed as a result of corona discharges on the insulator's surface. The acid caused the housing, fiber and resin to undergo corrosion. SEM imaging revealed fiber fracture surfaces with a morphology typical of stress corrosion cracking, showing that stress was part of the failure mechanism. The fracture of fibers and loss of resin led to a decrease in FRP rod strength and to failure. Highlights: An FRP insulator fractured as a result of a stress corrosion cracking (SCC) process. Corrosion occurred due to exposure of the housing and FRP rod-core to nitric acid. Acid was produced as a result of corona discharges, oxygen, nitrogen and water. The presence of contaminants on the housing enhanced corona discharge frequency. The failure caused a line outage and high losses to the electricity supplier.